Targeting innate and adaptive immunity to suppress lung cancer metastasis - Qin, Rong (Frontiers in Immunology, 2025)
Lung cancer remains the leading cause of cancer-related mortality globally, with metastasis and recurrence as the primary determinants of poor prognosis. Despite advances in immunotherapy, intrinsic and acquired resistance to immune checkpoint inhibitors (ICIs) underscores the need to explore alternative immunomodulatory strategies. Emerging evidence highlights the critical yet dual roles of innate and adaptive immune cells within the tumor microenvironment (TME) in either restraining or facilitating metastatic dissemination. Adaptive immunity, dominated by T and B cells, orchestrates context-dependent antitumor responses or immunosuppression, while innate immune dysregulation fosters metastatic niches. We highlight translational opportunities, such as natural killer (NK) cell activation, macrophage reprogramming, and dendritic cell (DC)-based vaccines, alongside prognostic biomarkers like peripheral NK activity and tryptase+ mast cell infiltration. This review summarizes the interplay of immune cell subsets, including T and B lymphocytes, macrophages, DCs, NK cells, and mast cells, in lung cancer progression. By synthesizing preclinical and clinical insights, this review identifies unresolved challenges and proposes targeting innate immunity as a promising avenue to augment current therapies and mitigate metastasis.